ASSESSING CARDIOVASCULAR SAFETY OF TESTOSTERONE REPLACEMENT THERAPY FOR MALE HYPOGONADISM: A SYSTEMATIC REVIEW AND META-ANALYSIS - Rachman, Manarul Iman Alfafa; Vilado, Irene Yasmina; Satriawan , Ilham; Lalchanzani , Jawaharlal Akbar; Faida, Nova Auliyatul; Permata , Angeline Asti Shiela; Nurhadi, Pradana; Daryanto, Besut (Indonesian Urological Association, 2024)
Objective: This study aims to comprehensively assess TRT's cardiovascular safety in males with hypogonadism, providing valuable insights for treatment decisions. Material & Methods: Adhering to PRISMA guidelines, we registered our PROSPERO protocol and analyzed relevant English-language randomized clinical trials published from 2008 to 2023. Results: Among 1187 initial papers, 7 studies met inclusion criteria, with 6 in quantitative analysis and all 7 in qualitative assessment. Our findings indicate that TRT does not significantly increase the risk of cardiovascular events compared to placebo. Specifically, the analysis of major adverse cardiac events (MACE) yielded an OR of 0.90 (95% CI: 0.74, 1.10; I² = 26%; p = 0.25), while the evaluation of all cardiovascular adverse events revealed an OR of 1.37 (95% CI: 0.73, 2.55; I² = 75%; p = 0.001). Conclusion: This study offers reassurance for clinical decision-making by suggesting that TRT is not significantly associated with an elevated cardiovascular risk in hypogonadal men, addressing the ongoing debates on this issue. Keywords: Cardiovascular safety, hypogonadism, testosterone replacement therapy.